An Overview of Urban and Regional Planning - Bahri Ergen, Yasar (IntechOpen, 2018)
Urban and regional planning is a spatial design practice that brings limitations to the intervention in natural areas to ensure a balance between population growth, housing, and employment in residential areas. It includes spatial design that enables living creatures to live while planning the interventions to ensure suitability to ecology, geology, climate, and land structure since intervention in nature should be balanced. In this context, the profession generally includes regional, spatial and urban planning, urban transformation that involves the urban decline areas in the city, urban renewal and protection, urban transportation, and urban management. Therefore, it is believed that this book will be useful for those who work in this area on a practical or academic basis and follow the innovations in the profession.